2019
DOI: 10.1085/jgp.201812162
|View full text |Cite
|
Sign up to set email alerts
|

Binding and structural asymmetry governs ligand sensitivity in a cyclic nucleotide–gated ion channel

Abstract: Hyperpolarization-activated cyclic nucleotide-gated (HCN) channels open more easily when cAMP or cGMP bind to a domain in the intracellular C-terminus in each of four identical subunits. How sensitivity of the channels to these ligands is determined is not well understood. Here, we apply a mathematical model, which incorporates negative cooperativity, to gating and mutagenesis data available in the literature and combine the results with binding data collected using isothermal titration calorimetry. This model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 59 publications
1
2
0
Order By: Relevance
“…It could be shown that mutations G660E, R669E and R710E led to an almost complete loss of whole cell fluorescence. This confirmed that these amino acids, supposed to directly interact with the ligand, are essential for binding [ 56 ]. Additionally, three amino acids not supposed to directly interact with the ligand were mutated.…”
Section: Early Career Researcher Presentationssupporting
confidence: 60%
“…It could be shown that mutations G660E, R669E and R710E led to an almost complete loss of whole cell fluorescence. This confirmed that these amino acids, supposed to directly interact with the ligand, are essential for binding [ 56 ]. Additionally, three amino acids not supposed to directly interact with the ligand were mutated.…”
Section: Early Career Researcher Presentationssupporting
confidence: 60%
“…Intriguingly, it had been suggested by Watson and Crick that small viral genome is more conducive to attaining protein multi-functionality via protein homooligomerization than by direct translation of large protein units (50). It is further noted that conformational symmetry or breakage is harnessed in several biological processes including ligand binding, nonspecific DNA binding, enzyme activation, and signaling (53)(54)(55)(56)(57).…”
Section: Allosteric Induction Of Homooligomeric Asymmetrymentioning
confidence: 99%
“…Intriguingly, it had been suggested by Watson and Crick that small viral genome is more conducive to attaining protein multi-functionality via protein homooligomerization than by direct translation of large protein units (50). It is further noted that conformational symmetry perturbation or breakage is harnessed in several biological processes including ligand binding, nonspecific DNA binding, enzyme activation, and signaling (53)(54)(55)(56)(57).…”
Section: Allosteric Induction Of Homooligomeric Asymmetrymentioning
confidence: 99%